Optimum ludnościowe jako remedium na zagrożenia demograficzne? Konfrontacja perspektywy globalnej i lokalnej - Wojciech JANICKI (Przegląd Geopolityczny)
Studies on the threat of depopulation or overpopulation, as well as the search for a population optimum for the Earth, are almost without exception conducted in isolation. The first indicate that the population of certain areas should be increased for socio-economic reasons. The second signal the need to drastically reduce the Earth's population because it has exceeded its capacity. The third finally focus on the search for an answer about optimal population for the Earth, generally indicating a value much lower than the current population of the planet. This paper juxtaposes the main streams of research on these three issues, in search of an answer to the question of the extent to which the population optimum is capable of ensuring the Earth's long-term stability in the context of the needs of ecological and geopolitical balance. It has been proposed to come to terms with the irreversibility of demographic changes accompanying social change, to appreciate the role of migration as a factor balancing and reconciling the demands of proponents of both extreme concepts.